Direito ao aborto e Constituição: gênero, identidade, diferença e jurisdição constitucional - André Freire Azevedo (2016)
This work aims to analyze abortion rights under the disciplinary perspective of constitutional law. The evaluated hypothesis is that the articles 124 and 126 of the Brazilian criminal code are subject to be declared partially unconstitutional, without text suppression, on the cases of their enforcement over elective abortions performed up to the end of the first trimester of pregnancy (or up to the thirteenth week of pregnancy). The first part of the work, divided into two chapters, contains theoretical and methodological considerations about scholar legal research on fundamental rights applied to the study of gender inequalities. The first chapter discusses linguistic turn in philosophy and its implications for the construction of a democratic human and fundamental rights theory, illustrated by the exemplary analysis of different theoretical approaches on the principle of human dignity. The second chapter discusses key concepts such as gender, subject and identity that will inform the analysis about how, during the ongoing process of interpreting the system of human and constitutional rights through the dialectical tension between identity and difference, law subjects with gendered markers are produced and reproduced, in an always precarious and contingent manner. The second part of the work is dedicated to the research itself and divided into five chapters. The third chapter contextualizes the works hypothesis and, more broadly, the matter of abortion in Brazil, in a historical and social fashion. The fourth chapter maps the institutional debate about sexual and reproductive rights set on the House of Representatives of the Brazilian Congress since the redemocratization, analyzing the way in which, since they make reference to a common horizon of fundamental rights and core concepts of constitutional law such as life, equality, liberty, autonomy, health etc., these discourses dispute a common place of enunciation of the identity of the constitutional subject. The fifth chapter debates two paradigmatic cases on life and abortion judged by the brazilian Supreme Court: the ADI 3.510 and the ADPF 54. The sixth chapter critically analyses on the light of constitutional law, the metaphoric discursive axis that seeks to find relations of equivalence and identity between embryos, fetuses and people, on all of its four main sub-axis: as a debate between the beginning of life; as a debate about if embryos and fetus have constitutional or human rights; as a discussion about the protection of life since its conception on the American Convention on Human Rights; and as a discussion about the legal or constitutional protection of the value of human life or of the objective dimension of life rights. The seventh chapter finally analyses the hypothesis of the present work on the light of the fundamental and human rights implied in the controversy, in a metonymic discursive axis that seeks to contextualize the variables involved in the matter of abortion rights. The work concludes, based on the notion of human dignity as the right to the recognition of moral autonomy based on the criteria of difference, that it must be recognized the unconstitutionality of applying criminal law to abortions performed on the first trimester of the pregnancy.